2013
DOI: 10.1088/0031-8949/2013/t157/014050
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and transport studies of plasticized chitosan-based proton conducting biopolymer electrolytes

Abstract: This paper focuses on the conductivity and transport properties of chitosan-based solid biopolymer electrolytes containing ammonium thiocyanate (NH 4 SCN). The sample containing 40 wt% NH 4 SCN exhibited the highest conductivity value of (1.81 ± 0.50) × 10 −4 S cm −1 at room temperature. Conductivity has increased to (1.51 ± 0.12) × 10 −3 S cm −1 with the addition of 25 wt% glycerol. The temperature dependence of conductivity for both salted and plasticized systems obeyed the Arrhenius rule. The activation ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
2
19
0
2
Order By: Relevance
“…B3 sample). This is because glycerol possesses a high dielectric constant which can weaken the Coulombic force between cation and anion of the salt hence more undissociated salt becomes free mobile ions [29]. Furthermore, the addition of plasticizer can create more pathways for ion conduction and can also increase ionic mobility [30,31].…”
Section: Ftir Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…B3 sample). This is because glycerol possesses a high dielectric constant which can weaken the Coulombic force between cation and anion of the salt hence more undissociated salt becomes free mobile ions [29]. Furthermore, the addition of plasticizer can create more pathways for ion conduction and can also increase ionic mobility [30,31].…”
Section: Ftir Studiesmentioning
confidence: 99%
“…Furthermore, the addition of plasticizer can create more pathways for ion conduction and can also increase ionic mobility [30,31]. Shukur et al [29] reported that when ethylene carbonate (EC) was added to the starch-chitosan-NH 4 Br based electrolytes, the conductivity increased from 9.72 × 10 −5 to 1.44 × 10 −3 S cm −1 . From Fig.…”
Section: Ftir Studiesmentioning
confidence: 99%
“…ion and the conduction occur through the exchange of ions between complexed sites. Preparation of biopolymer based chitosan with ammonium thiocyanate (NH 4 SCN) has attracted many researchers for the development of high conducting biopolymer electrolyte [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the ions require less energy to hop over to the next site. The plasticization method also can dissociate more salt to become ions which contributes towards ionic conduction [29]. The conductivity of ∼ 10 −7 S cm −1 of a chitosan-lithium acetate (LiOAc) electrolyte was increased to 5.5 × 10 −6 S cm −1 when plasticized with palmitic acid [30,31].…”
Section: Introductionmentioning
confidence: 99%